2018
DOI: 10.3390/medicina54050091
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sleep Quality and Body Composition in Sedentary Middle-Aged Adults

Abstract: Background: Ageing is associated with sleep pattern changes and body composition changes, which are related to several diseases. Purpose: This study aimed to analyse the association between sleep quality and an extensive set of body composition parameters (waist-hip ratio, body mass index, bone mineral content, bone mineral density, lean mass, lean mass index, fat mass, fat mass percentage, fat mass index, visceral adipose tissue) and sleep quality in sedentary middle-aged adults. We also aimed to evaluate whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 49 publications
5
28
1
1
Order By: Relevance
“…According to our results, higher values of WHiR were associated with shorter sleep duration, lower sleep efficiency and increased time awake after sleep onset. These results are in accordance with previous research emphasizing that, besides being major risk factors for cardiometabolic alterations, cancer and all-cause mortality [58,59], WHiR and abdominal obesity are significantly related to severe sleep disturbances such as short sleep duration and obstructive sleep apnoea [23,60], especially in younger adults [58]. Regarding LMI, we found that those participants with higher LMI exhibited shorter sleep and lower sleep efficiency.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…According to our results, higher values of WHiR were associated with shorter sleep duration, lower sleep efficiency and increased time awake after sleep onset. These results are in accordance with previous research emphasizing that, besides being major risk factors for cardiometabolic alterations, cancer and all-cause mortality [58,59], WHiR and abdominal obesity are significantly related to severe sleep disturbances such as short sleep duration and obstructive sleep apnoea [23,60], especially in younger adults [58]. Regarding LMI, we found that those participants with higher LMI exhibited shorter sleep and lower sleep efficiency.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding LMI, we found that those participants with higher LMI exhibited shorter sleep and lower sleep efficiency. Although controversial to previous studies where LMI was positively associated with sleep quality [23], these results may be explained by evidence exposing that lower LMI was related to longer or excessive sleep duration, potentially due to increased levels of cortisol triggered by sleep disturbances which, in turn, has been related to muscle degradation [61].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…It has been previously reported that PSQI and accelerometer records measure different attributes of sleep, highlighting the bias of accelerometry to register wakefulness, thus lying in bed awake but motionless is likely to be coded as sleep 63 . Therefore, it is recommended to use both methods to obtain complementary information additionally to the body movements 64 . These differences in measurement of sleep attributes could explain the different results of the associations between sleep quality and energy metabolism.…”
Section: Discussionmentioning
confidence: 99%